High-Gain Seven-Level Switched-Capacitor Two-Stage Multi-Level Inverter - Ahmed, Hassan Yousif; Abdel-Rahim, Omar; Ali, Ziad M. (Frontiers in Energy Research, 2022)
Due to the low voltage of the PV module and to enable ac module technology, where every PV module has its own dc-ac converter, this paper introduces a new high step-up seven-level two-stage multilevel inverter for grid-connected photovoltaic (PV) system. The introduced schematic consists of two stages. The first stage is a switched capacitor boost converter and the second stage is a seven-level seven-switches multilevel inverter. The first stage is designed to extract the maximum power of the PV module and step up its input voltage. the proposed seven-level seven-switches topology generates seven-level with only seven switches. Thus, the number of switches is reduced. The proposed inverter has eight valid switching states. In each switching state, only three switches are ON at the same time. The proposed topology has some distinct features such as a reduced number of switches and reduced conduction. The developed system is simulated in MATLAB/SIMULINK and experimentally demonstrated using DSPACE1202. Both simulation and experimental results are consistent with the theoretical analysis.